Amino acid assisted growth of CuO nanostructures and their potential application in electrochemical sensing of organophosphate pesticide. (1st February 2016) - Soomro, Razium Ali; Hallam, Keith Richard; Ibupoto, Zafar Hussain; Tahira, Aneela; Sherazi, Syed Tufail Hussain; Sirajjuddin; Memon, Safia Sanam; Willander, Magnus
Abstract: This work reports a highly sensitive electrochemical sensor for organophosphate pesticide (malathion) based on unique and attractive CuO nanostructures. The discussed nanostructures were synthesized using low temperature hydrothermal growth method utilizing green amino acids such as glycine, serine, threonine and histidine as effective bio-compatible templates. The morphological evaluation demonstrated formation of unique and attractive 1-D nanostructures reflecting the effective growth controlling and directing capabilities of the utilized amino acids. The as-synthesized CuO nanostructures were noted to possess high affinity towards malathion which enabled their application as electrode material for the development of affinity based electrochemical sensor. Although, the as-synthesized morphologies were all sensitive towards malathion but the glycine directed triangular flake-like nanostructures exhibited greater sensitivity compared to other competitors. The electrochemical behaviour of the modified electrodes was studied using cyclic voltammetry (CV) whereas, differential pulse voltammetry (DPV) was utilized for the analytical evaluation of the sensor. The developed sensor demonstrated high reproducibility, stability, wide detection window (1–12 nM), and sensitivity to detect malathion up to 0.1 nM based on suppressive signal measurement. In addition, the sensor system exhibited high anti-interference capability in the presence of common co-existing pesticides like lindane, carbendazim, and trichlorfon. The developed sensor provides an effective measure for detecting extremely low concentration of malathion with wide applicability in various fields.